Magnetism of outdoor and indoor settled dust and its utilization as a tool for revealing the effect of elevated particulate air pollution on cardiovascular mortality - Diana Jordanova; Neli Jordanova; Philippe Lanos; Petar Petrov; Tsenka Tsacheva (Geochemistry, Geophysics, Geosystems, 2012)
Settled indoor and outdoor dusts in urban environment represent an important source of secondary pollution. Magnetic characteristics of the settled dust from six cities in Bulgaria are explored, allowing comparison on a national (country) scale. Monthly variations of the mass‐specific magnetic susceptibilities (χindoor) and (χoutdoor) and calculated dust loading rates for a period of 17 months do not show seasonal variability, probably due to the dominant role of traffic‐related emissions and soil‐derived particles in the settled dust. The main magnetic mineral is magnetite, present as spherules and irregular particles of pseudo‐single‐domain grain sizes. Systematically lower remanence coercivities are obtained for outdoor dusts when compared with the corresponding indoor samples, implying that penetration of smaller particles of ambient origin indoors is the main source of the indoor dust. Mean yearly values of the ratio (χindoor/χoutdoor) for each city show statistically significant correlation with mortality due to cardiovascular diseases. This ratio reveals the source‐ and site‐specific importance of the anthropogenically derived toxicogenic fraction. Heavy metal content of the settled dust is related to the contribution from several pollution sources (soil‐derived, combustion and industrial), discriminated through analysis of principal components. SEM/EDX analyses reveal abundant presence of anthopogenic Fe‐containing spherules, irregular particles and diesel exhaust conglomerates. High molecular weight polyaromatic hydrocarbons (PAH) dominate the total PAH content of the outdoor dust samples. The observed linear correlation between total PAH content, coercivity of remanence and the ratio Mrs/χ suggest either adsorption of PAHs on iron oxide particles and especially magnetite, or emission related increase in total PAH concentration along with a decrease of effective magnetic grain size of the accompanying magnetic fraction.